Revisiting the Formation and Radicalisation of Boko Haram and Al-Qaeda in the Lands of the Islamic Maghreb (AQIM) through Social Movement Theory - Danguguwa, Kabiru Ibrahim; Hotoro, Bello Adamu; Kabara, Bello Sani (European Scientific Journal, ESJ, 2024)
This paper uses social movement theory to examine the rise and development of Boko Haram and AQIM into radical groups. Boko Haram and AQIM were initially established as moderate and conservative Islamist groups in Nigeria and Algeria respectively. AQIM was originally a political party – the FIS but changed names to the GIA, the GSPC, and AQIM each with a different modus operandi. Boko Haram was a local organization that has been espousing an anti-system frame alongside violent tactics since 2009. Relying on secondary data, this paper found that the emergence and eventual transformation of Boko Haram and AQIM into radical movements signify the existence of social movement factors of political opportunity structures, mobilizing structures, and framing processes in Nigeria and Algeria. Results from content analysis of the data show that while the two movements emerged in two distinct socio-economic and political environments, they were rational actors who continued to utilize the available political structures opportunity, mobilizing structures and framing processes to mobilize and sustain collective actions. It is evident that government repression only made the two groups change tactics and strategies when what they regarded as free spaces diminished at times they gathered material and non-material resources. That coincided with the radical views of some of the groups’ members, the presence of mobilizing structures, and a frame resonance that ensured recruitment into the two movements.